2005
DOI: 10.1126/science.1108595
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Mechanisms of Signal Transduction

Abstract: Forty years ago, a simple model of allosteric mechanisms (indirect interactions between distinct sites), used initially to explain feedback-inhibited enzymes, was presented by Monod, Wyman, and Changeux. We review the MWC theory and its applications for the understanding of signal transduction in biology, and also identify remaining issues that deserve theoretical and experimental substantiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
554
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 691 publications
(581 citation statements)
references
References 32 publications
20
554
0
7
Order By: Relevance
“…cellular localization or content and concentrations of co-regulatory molecules), and liganddependent or independent post-translational modifications, different concentrations of the ligand pools may be required to stabilize the ensemble threshold required to trigger or induce a given intracellular signaling cascade or global cellular event. Finally, while the model presented seems consistent with stereo and shape specific vitamin D sterol-VDR structurefunction results and an overlapping two pocket allosteric model [52], it remains a hypothetical model until true kinetic and/or structural validation is obtained to further substantiate presence of a VDR A-pocket. figure).…”
Section: Discussionsupporting
confidence: 59%
“…cellular localization or content and concentrations of co-regulatory molecules), and liganddependent or independent post-translational modifications, different concentrations of the ligand pools may be required to stabilize the ensemble threshold required to trigger or induce a given intracellular signaling cascade or global cellular event. Finally, while the model presented seems consistent with stereo and shape specific vitamin D sterol-VDR structurefunction results and an overlapping two pocket allosteric model [52], it remains a hypothetical model until true kinetic and/or structural validation is obtained to further substantiate presence of a VDR A-pocket. figure).…”
Section: Discussionsupporting
confidence: 59%
“…1 Later studies, both in bulk and with single molecule resolution, proposed monomeric proteins to operate through conformational selection. 3,38,40−45 The same mechanism was successfully borrowed for monomeric enzymes to explain substrate mediated conformational redistributions along the reaction coordinate.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…In this study, we found that egonol gentiobioside and egonol gentiotrioside at concentrations of 0.1-1 mM could significantly promote the substrate conversion catalyzed by purified aromatase in vitro, indicating that the binding of these compounds may modulate the protein conformation of aromatase and enhance its substrate conversion efficiency. This positive allosteric effect has been widely found in ligand-binding receptors and enzyme catalysis (Changeux and Edelstein, 2005). It has been reported that aromatase activity is enhanced by posttranslational modification through the mitogen-activated protein kinase or phosphoinositide 3-kinase pathway (Miller et al, 2008;Su et al, 2011).…”
Section: Discussionmentioning
confidence: 92%